Large variation in use of patient-reported outcome measures: A survey of 188 foot and ankle surgeons. Issue 3 (June 2018) - Zwiers, R.; Weel, H.; Mallee, W.H.; Kerkhoffs, G.M.M.J.; van Dijk, C.N.; ,; Ramos, Acacio J.C.; Ajis, Adam; Toom, Alar; Ortolani, Alessandro; Russo, Alessandro; Abdelwahab, Ali; et al.
Highlights: The majority of foot and ankle surgeons uses patient-reported outcome measures. A wide variety of outcome measures is used, there is no consensus amongst foot and ankle surgeons. The AOFAS Hindfoot scale is still most popular outcome measure in foot and ankle disorders. Most popular PROMs are the MOXFQ and FAOS. Abstract: Background: There is an increasing interest in the use of patient reported outcome measures (PROMs). However, there is a large variety of PROMs and a lack of consensus regarding preference for their use. Aim of this study is to determine how often PROMS are used for foot and ankle disorders, for what purpose PROMs are used, and what the preferences of the foot and ankle surgeons are, when choosing a PROM to use. Methods: Members of the Ankleplatform Study Group—Science of Variation Collaborative were invited to participate in this survey by email. The online survey consisted of six questions on the use and preferences regarding foot and ankle PROMs. Results: 188 participants completed the questionnaire. Of the respondents 17% reported not to use PROMs, 72% stated to use PROMS for research, 39% routinely for patient care and 34% for registration or quality assessment. The respondents were familiar with 30 different outcome measures, of which 20 were PROMs. One of the excluded outcome measures, the AOFAS Hindfoot scale was most commonly reported as preferred outcome measure. FAOS and MOXFQ were the preferred PROMs, reported by 9.7% of the surgeons. Subsequently followed by the FFI (4.3%), the FAAM (3.7%) and the VAS-FA (3.7%). Conclusions: A large majority of the foot and ankle surgeons uses PROMs. The AOFAS hindfoot scale is mentioned as the most preferred outcome measure, while in fact this is not a PROM. Of the twenty different PROMs mentioned in this study, most reported were the FAOS and MOXFQ both supported by only 9.7% of the surgeons. For proper comparison between patients in clinical practice and research, consensus is needed on which easy-to-use PROM with adequate clinimetric properties should be used. Therefore more evidence in the field of clinimetrics of foot and ankle outcome measures is needed.